New Evidence on Cyclical Variation in Labor Costs in the U.S. - Grace Weishi Gu; Eswar Prasad (Institute of Labor Economics (IZA), 2018)
Employer-provided nonwage benefit expenditures now account for one-third of U.S. firms' labor costs. We show that a broad measure of real labor costs including such benefit expenditures has become countercyclical during 1982-2014, contrary to the conventional view that labor costs are procyclical. Using BLS establishment-job data, we find that even real wages, the main focus of prior literature, have become countercyclical. Benefit expenditures are less rigid than nominal wages, although both components of labor costs have become more rigid. These rigidities, along with the rising relative importance of aggregate demand shocks (including the financial crisis), help explain countercyclical labor costs.
Keywords: E24; J32; E32; 330; wages; benefits; compensation; economic fluctuations; cyclicality